Directions of formalization management of technical equipment's inviolable inventory in the sections of The State Special Transportation Service of Ukraine - Radkevych, A. V.; Stepanenko, O. O.; Shchoka, I. M.; Yakovliev, S. O. (Science and Transport Progress, 2010)
The directions to formalization of management of the inviolable reserves of technical facilities in subdivisions of the Derzhspetstranssluzhba (State Special Transport Service) for the increase of efficiency level of realization of the tasks put before them are considered.